Bioinformatics and Expression Profiling of the DHHC-CRD S-Acyltransferases Reveal Their Roles in Growth and Stress Response in Woodland Strawberry (Fragaria vesca) - Si Gu; Xinghua Nie; Amal George; Kyle Tyler; Yu Xing; Ling Qin; Baoxiu Qi (Plants)
Protein S-acyl transferases (PATs) are a family of enzymes that catalyze protein S-acylation, a post-translational lipid modification involved in protein membrane targeting, trafficking, stability, and protein–protein interaction. S-acylation plays important roles in plant growth, development, and stress responses. Here, we report the genome-wide analysis of the PAT family genes in the woodland strawberry (Fragaria vesca), a model plant for studying the economically important Rosaceae family. In total, 21 ‘Asp-His-His-Cys’ Cys Rich Domain (DHHC-CRD)-containing sequences were identified, named here as FvPAT1-21. Expression profiling by reverse transcription quantitative PCR (RT-qPCR) showed that all the 21 FvPATs were expressed ubiquitously in seedlings and different tissues from adult plants, with notably high levels present in vegetative tissues and young fruits. Treating seedlings with hormones indole-3-acetic acid (IAA), abscisic acid (ABA), and salicylic acid (SA) rapidly increased the transcription of most FvPATs. A complementation assay in yeast PAT mutant akr1 and auto-S-acylation assay of one FvPAT (FvPAT19) confirmed its enzyme activity where the Cys in the DHHC motif was required. An AlphaFold prediction of the DHHC and the mutated DHHC155S of FvPAT19 provided further proof of the importance of C155 in fatty acid binding. Together, our data clearly demonstrated that S-acylation catalyzed by FvPATs plays important roles in growth, development, and stress signaling in strawberries. These preliminary results could contribute to further research to understand S-acylation in strawberries and plants in general.